UJI PERBEDAAN DOSIS NPK MUTIARA TERHADAP PERTUMBUHAN DAN PRODUKSI TOMAT LAHAN KERING - Neonufa, Nimrot Eli. M; Kuang, Stefanus M.; Pandu, Marvin J. (AGRICA, 2025)
Tomato plants are easy to cultivate because they have high adaptability and a relatively short lifespan. Efforts to develop tomatoes at the farmer level are carried out by improving soil nutrient conditions by providing various types of organic and inorganic fertilizers in order to accelerate the growth process, development and production of tomato. Adequate nutrients will stimulate leaf and stem growth, budding, chlorophyll formation, increase nutrient absorption, and have an important effect on increasing yields. This research was conducted in the dry land of Kaniti village from July to September 2024. The tools and materials used in the study were hoes, watering cans, digital scales, rulers, knapsack sprayers, calipers, cameras, hybrid tomato seeds, polybags, bokashi, curacron (insecticide), NPK Mutiara, stakes, and ropes/twines. The study used a Completely Randomized Design (CRD), with one independent variable in the form of a dose of NPK Mutiara compound fertilizer at four treatment levels: no fertilizer (control), 2 g (H1), 4 g (H2), and 6 g (H3) per plant. The dependent variables included growth parameters—plant height, stem diameter, and number of productive branches—measured at 14, 28, 42, and 56 days after planting (DAP), with data from 56 DAP analyzed as a representation of final growth. Production parameters consisted of weight and number of fruits per plant, measured at 72, 78, 85, and 90 DAP, with the average value or total harvest used in the analysis. Significant differences between doses of NPK Mutiara compound fertilizer were analyzed using one-way ANOVA. Further tests were conducted using post-hoc (DMRT). The results showed that treatment H3 (6g NPK Mutiara/plant) gave the best performance in most growth and production parameters, indicating a positive dose-response relationship within the tested range. Application of NPK Mutiara of 6g/plant—with repetitions on days 0, 14, and 28 DAP—significantly increased tomato growth and yield compared to the control, although it was not significantly different from the 4g dose in the 5% LSD test. The results of further tests confirmed that treatment H3 (6g NPK Mutiara/plant) was significantly superior (group A) to H2, H1, and H0 in increasing plant height and production parameters (weight and number of fruits). This indicates a positive dose-response relationship within the range of doses tested, with a dose of 6 grams/plant proving to be the most effective in increasing tomato productivity.